Atypical presentation of typical carcinoid. (17th January 2014) - El-Kersh, Karim; Gauhar, Umair; Saad, Mohamed
Abstract : Bronchial carcinoid tumours can present with symptoms of distal airway obstruction, local airway irritation or bleeding due to hypervascularity. Presentation with a spontaneous pneumothorax (SP) is rare. We present a case of typical endobronchial carcinoid tumour that presented with a SP. We explored the possible mechanisms of this rare presentation, especially the check-valve mechanism of airway obstruction, which was evident during the fiberoptic bronchoscopic examination.